Estimates of the probability of reversibility of random polynomials used in the modified version of NTRU cryptosystem - Алексейчук, А.Н.; Матийко, А.А. (Radiotekhnika, 2017)
Using the trigonometric sums method we obtain analytical bounds for the probability of reversibility of polynomials used as secret keys in a modified version of NTRU encryption scheme. We show that the obtained bounds are applicable in practice to choosing the long-term parameters of the encryption scheme.